Identification of pathologies and maintenance techniques in a semi-buried reservoir - Jizuato , João Victor Pereira; Gregui , Ana Paula Moreno Trigo (Seven Editora, 2023)
In the structured reservoirs of reinforced concrete, among the most incident pathological manifestations are the corrosion of the reinforcements, cracks and cracks in the roof or bottom slab, infiltrations and deterioration of the concrete. Identifying such pathologies is essential to ensure the safety, durability and efficiency of the structures, as well as to avoid excessive expenses and waste of resources during the recovery of the same. This article aims to present the pathologies in semi-buried water reservoirs of reinforced concrete, taking as an example a Votuporanga reservoir, and to analyze possible recovery techniques to be applied. After sensory analysis of the reservoir under study, several pathologies were identified, such as cracks, cracks, deterioration of waterproofing, peeling of paint, corrosion of the pipe, mold and mildew. Based on the diagnoses, procedures such as resin injection, cleaning and painting of oxidized metal elements, mold removal and application of waterproofing can be performed. The proper use of maintenance techniques and appropriate materials prove to be effective in the rehabilitation of reservoirs, ensuring water quality and extending the useful life of structures. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-094